Eccentric compression performance of composite columns composed of RAC-filled circular steel tube and profile steel. (15th December 2019) - Ma, Hui; Chen, Yunchong; Bai, Hengyu; Zhao, Yanli
Highlights: Failure modes and force mechanism of the composite columns under eccentric compressive loads. The effects of parameters on the eccentric compression performance of the composite columns. The calculation formulas suitable for the eccentric bearing capacity of the composite columns. Abstract: To study the eccentric compression performance of composite columns composed of recycled aggregate concrete (RAC)-filled circular steel tube and profile steel, 17 static loading tests of the columns under eccentric compression loading were performed in this study. The design parameters of these columns were recycled coarse aggregate (RA) replacement percentage, diameter–thickness ratio of circular steel tube, profile steel ratio, eccentricity, RAC strength grade, slenderness ratio and section form of profile steel. The load–lateral displacement curves, load–strain curves, lateral deflection and bearing capacity of the columns were established and assessed in detail. The results showed that the failure of the columns began with the yield of profile steel in the middle of compression side, and then the yield strength of circular steel tube was reached at the compression side. Subsequently, the core RAC was crushed, and local buckling occurred in the middle of the circular steel tube, thereby resulting in the loss of the eccentric bearing capacity of the columns. The eccentric bearing capacity of the columns decreased with the increase in RA replacement percentage. Reducing the diameter–thickness ratio of circular steel tube and increasing the profile steel ratio can improve the eccentric bearing capacity of the columns. Meanwhile, the increase in eccentricity and slenderness ratio was disadvantageous to the eccentric bearing capacity of the columns. In summary, the columns generally show good ductile deformation capacity and high eccentric bearing capacity. On the basis of the failure mechanism and calculation model of these columns, the calculation formulas suitable for the eccentric bearing capacity of the columns were deduced, and the calculation results were verified compared with the test results.